STRENGTHENING EXERCISE UNTUK MENGURANGI NYERI LUTUT PADA LANSIA DENGAN OSTEOARTHRITIS DI POSYANDU 6SPM - Fatih Ijlal; Rinche Sekar; Apriliyan Yunita; Widya Laitupa; Rio Dwi; Feliza Tri; Umi Rahmawati; Rini Widarti (CV. Denasya Smart Publisher, 2026)
Knee osteoarthritis is a degenerative joint disease characterized by cartilage damage, subchondral bone changes, and osteophyte formation, causing pain, stiffness, reduced range of motion, and joint dysfunction. This community service program aims to increase the knowledge of elderly people about strengthening exercises to reduce pain in elderly people with knee osteoarthritis and the use of leaflets as a self-help guide at home. Methods: The educational activities included lectures, interactive discussions, and practical demonstrations that were effective in increasing the knowledge of the elderly about treatments to reduce pain in the elderly with knee osteoarthritis and the use of leaflets as a self-guide home reference. The target of the activity was 24 elderly people with knee osteoarthritis pain. Results: The results of the evaluation through pre-test and post-test showed an increase in the understanding of the elderly. Before the counseling, only 20% of the elderly knew about strengthening exercises to reduce knee osteoarthritis pain. After the counseling and demonstration, there was an increase to 100% of the elderly demonstrated knowledge strengthening exercises to reduce knee osteoarthritis pain and were able to practice the exercises correctly. Conclusions: Education on strengthening exercises to reduce knee osteoarthritis pain is conducted through lectures, interactive discussions, and practical demonstrations that are effective in increasing the knowledge of older adults regarding treatment to reduce pain in older adults with knee osteoarthritis.